Angiomyolipoma with epithelial cysts (AMLEC): a rare but distinct variant of angiomyolipoma - Rao Uma NM; Yin Ming; Armah Henry B; Parwani Anil V (BMC, 2007)
Abstract Angiomyolipoma with epithelial cysts (AMLEC) is a recently described distinct cystic variant of angiomyolipoma (AML). To date 15 cases of AMLEC have been reported in 2 case series. We report the 16th case in a 39-year-old female. Her left kidney tumor was discovered incidentally. Partial nephrectomy was performed. Histologically, the tumor was composed of three components: 1) epithelial cysts lined by cuboidal to hobnail cells; 2) compact subepithelial mullerian-like AML stroma with admixed chronic inflammation; and 3) muscle-predominant AML with dysmorphic blood vessels exterior to the subepithelial stroma. Immunohistochemically, the subepithelial stroma stained most intensely with HMB-45 and Melan-A, whilst the muscle-predominant AML areas stained most intensely with smooth muscle actin and desmin. Estrogen receptor (ER), progesterone receptor (PR), and CD10 stained most intensely in the subepithelial stroma. The cyst lining was positive for pancytokeratin, but negative for HMB-45, Melan-A, ER, PR, and CD10. The patient is alive with no evidence of disease, 12 months postoperatively, and yearly follow-up CT scans are planned.